Legal system before the challenges of technological progress: introduction, Criminal law and technology, criminal law principles in the face of the challenges of new technologies, digital evidence, technology and civil law, subjects of civil law, the impact of technology on the protection of human rights, the rule of law and technology, conclusion, - Primorac, Magdalena (Glasnik Advokatske komore Vojvodine, 2025)
Modren society builds its foundations for the future on technology and science. Accelerated technological and scientific progress is changing the atter that the legal system regulates or should regulate. The development of new technologies with a special emphasis on the development and application of AI in the field of law opens revolutionary questions. Whit that, peper will analyze the impact of technology on the field of criminal and civil law, and the challenges of protecting human rights in the digital age by applying the following scientific methods: compilation, literature analysis, synthesis, classification and delphi methods. Investigation and prosecution of digital crimes requries respect for fair legal principles and procetion of individual rights. New technologies put pressure on the legal system, wich under this pressure violates basic legal prniciples. Contemporary legal challenges lead to tectonic shifts in the field of law. The paper analyzes the impact of AI and algorithms on the rule of law, and analyzes fundamental legal principles. This is not the first time that legal sistems are faced with regulating an inanimate system that has no consciousness and capacity fot guilt. The key question is whether we are ready for the revolutionary step of introducing a third legal entity-an electronic person?